2015
DOI: 10.3892/ol.2015.3216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the duration of hormonal therapy following radiotherapy for localized prostate cancer

Abstract: Abstract. External-beam radiotherapy (EBRT) combined with androgen deprivation therapy (ADT) is known to provide improved survival outcomes compared with EBRT alone in the treatment of prostate cancer; however, the use of ADT has been reported to be associated with adverse events. Accordingly, the aim of the present study was to clarify the adequate duration of ADT when combined with EBRT to treat patients with high-risk localized prostate cancer, with consideration of survival outcomes and toxicity. Between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Therefore, we could not draw a conclusion that CVD is more likely to happen in 5 years. The results from Mitsuru et al in terms of a large cohort are similar to ours, and they suggested that the incidence of cardiac events was significantly higher among patients treated with short‐term ADT (<3 year) compared with patients treated with long‐term ADT(>3 year) ( P < .01). In another observational study, Efstathiou et al found no evidence to prove that longer‐term ADT increased cardiovascular mortality compared with short‐term ADT in men with locally advanced PCa.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, we could not draw a conclusion that CVD is more likely to happen in 5 years. The results from Mitsuru et al in terms of a large cohort are similar to ours, and they suggested that the incidence of cardiac events was significantly higher among patients treated with short‐term ADT (<3 year) compared with patients treated with long‐term ADT(>3 year) ( P < .01). In another observational study, Efstathiou et al found no evidence to prove that longer‐term ADT increased cardiovascular mortality compared with short‐term ADT in men with locally advanced PCa.…”
Section: Discussionsupporting
confidence: 83%
“…This supports the opinion that those patients threated with ADT and an preexisting CV disease may be at the greatest risk (2)(3)(4)(5)33). Increased cardiovascular toxicity in patients undergoing a short-term ADT was confi rmed by another authors (38). During long-term agonist therapy the loss of GnRH receptor sensitivity may occur what can be accompanied with renewal of testosterone production (24) and this fact may partially clarify these results.…”
Section: Clinical Studiessupporting
confidence: 63%
“…In another study, significant difference was observed in the 5-year biochemical PFS rates between short- (<36 months) and long-term (≥36 months) ADT (84.0% vs. 96.2%; P=0.04). However, the difference in OS was not significant (86.8% vs. 94.4%; P=0.16) (40). In our study, the majority of the patients (66.6%) received CAB, followed by AA (27.0%) and LHRHa (6.9%) for median 20 months.…”
Section: Discussionmentioning
confidence: 99%